2022
DOI: 10.3390/math10071118
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Wind Distribution around Buildings in Low-Density Urban Community

Abstract: The computational fluid dynamics (CFDs) models based on the steady Reynolds-averaged Navier–Stokes equations (RANSs) using the k−ω two-equation turbulence model are considered in order to estimate the wind flow distribution around buildings. The present investigation developed a micro-scale city model with building details for the Hail area (Saudi Arabia) using ANSYS FLUENT software. Based on data from the region’s meteorological stations, the effect of wind speed (from 2 to 8 m/s) and wind direction (north, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is important to note that all the results are based on an effort to faithfully replicate real-world conditions. For this purpose, several parameters, such as wind direction [ 24 ] and pollutant emission velocity from the chimney, were kept constant. However, the wind velocity profile, in particular the reference velocity “u ref ” was varied from 0 to 10 m/s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that all the results are based on an effort to faithfully replicate real-world conditions. For this purpose, several parameters, such as wind direction [ 24 ] and pollutant emission velocity from the chimney, were kept constant. However, the wind velocity profile, in particular the reference velocity “u ref ” was varied from 0 to 10 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…For the turbulent kinetic energy, “I" represents the turbulence intensity estimated at 5 % for the climatic condition of Hail region [ 24 ]. Finally, the terms d and Ht in the specific dissipation rate equations, represent respectively the hydraulic diameter of the stacks and the altitude of the whole studied area.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 11b shows that the TKE value exhibits a large peak near the RT location. This implies that large velocity fluctuations occurred [41]. The results at the section plane across the WT location are shown in Figure 11c,d.…”
Section: General Flow Patternmentioning
confidence: 91%
“…Hnaien developed a city model with building details for the Hail region and conducted CFD simulations to identify areas with low wind comfort. The results showed that the weather conditions (wind speed and direction) and building layout significantly affected comfort [14]. Vita combined CFD and dynamic thermal modeling (DTM) to assess the airborne infection risk in buildings and make buildings safer during an epidemic [15].…”
Section: Introductionmentioning
confidence: 99%